2010
DOI: 10.1371/journal.pone.0009883
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting Species without Nuclear Monophyly in Madagascar's Mouse Lemurs

Abstract: BackgroundSpeciation begins when populations become genetically separated through a substantial reduction in gene flow, and it is at this point that a genetically cohesive set of populations attain the sole property of species: the independent evolution of a population-level lineage. The comprehensive delimitation of species within biodiversity hotspots, regardless of their level of divergence, is important for understanding the factors that drive the diversification of biota and for identifying them as target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(184 citation statements)
references
References 65 publications
9
174
1
Order By: Relevance
“…However, the conferral of species status is dependent upon the consensus across multiple gene trees (Taylor et al, 2000). In a study of mouse lemurs (Weisrock et al, 2010), species were identified with the aid of the GSI despite little evidence of monophyly amongst individual gene regions. In the current study the combined gene tree is monophyletic for all species (GSI results) and all species level nodes have high statistical support for both bootstrap and bayesian analyses confirming species level classification for all named species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conferral of species status is dependent upon the consensus across multiple gene trees (Taylor et al, 2000). In a study of mouse lemurs (Weisrock et al, 2010), species were identified with the aid of the GSI despite little evidence of monophyly amongst individual gene regions. In the current study the combined gene tree is monophyletic for all species (GSI results) and all species level nodes have high statistical support for both bootstrap and bayesian analyses confirming species level classification for all named species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a new statistical method, the Genealogical Sorting Index (GSI) has been introduced (Cummings et al, 2008). The usefulness of this method has been demonstrated in studies investigating cryptic species in lemurs (Weisrock et al, 2010) and determining lineages in rice, despite incomplete lineage sorting and introgression/hybridisation events (Cranston et al, 2009). In each case, the GSI provided additional objective information for clarifying the relationship between genetic lineages.…”
Section: Introductionmentioning
confidence: 99%
“…For the cmyc2 fragment, we calculated the gsi for 100 trees, which were randomly selected from the Bayesian posterior distribution of trees. These 100 individual gsi were then used to calculate an ensemble gsi statistic (gsi T ), which represents a summary of the index across the Bayesian posterior distribution (Weisrock et al, 2010). The significance of all gsi T statistics was assessed using 1000 randomization permutations.…”
Section: Partitionmentioning
confidence: 99%
“…These values (0.36-0.69) are comparable to specieslevel divergence suggested by previous studies. For example, of the 16 mouse lemur species Weisrock et al (2010) defined, the majority of gsi T values are between 0.2-0.5 and some values of individual loci is as low as 0.12. Similarly, Fusinatto et al (2013) reported Euparkeralla frog species with gsi values of 0.55-0.58 for some nuclear loci.…”
Section: Species Diversity In the Amolops Mantzorum Groupmentioning
confidence: 99%
“…Wiens and Penkrot 2002); (4) BAT, the Bayesian Assignment Test, which is based on the combination of population genetic and genealogical patterns across multiple loci, recognizing species according to concordance between mtDNA clades and patterns of nuclear population structure (cf. Weisrock et al 2010); (5) HW, the Haploweb approach, which is based on haplotype networks with additional connections between haplotypes found co-occurring in heterozygous specimens (haplowebs) to delineate species boundaries (cf. Doyle 1995, Flot et al 2010; (6) BSD, the Bayesian Species Delimitation, which is based on coalescence theory, and uses bipartitions of specimens in gene trees that are shared across loci to infer species-level lineages (cf.…”
Section: Introductionmentioning
confidence: 99%